Analisis Pengaruh Resiko Bisnis,Profitabilitas dan Karakteristik Perusahaan terhadap Peringkat Obligasi dengan Struktur Modal sebagai Variabel Mediasi pada Perusahaan Perbankan BEI 2016-2021 - Evi Jayanti; Risal Rinofah; Ratih Kusumawardhani (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
The goal of this study is to investigate how bond ratings are influenced by business risk, profitability, company size, and company growth on bond rating through the use of capital structure. The population of this study is made up of PT Indonesian Rating Agency and the banking businesses listed on the Indonesia Stock Exchange for the years 2016 through 2021. Purposive sampling was the method of sampling that was used. The information used was gathered through the use of secondary data and library research methods. The Sobel test, the Path Analysis method, and the SPSS version 26 application were used in this study's data analysis at 15 different companies. The findings of this study suggest that, while profitability has no effect on bond ratings, business risk, company size, and company growth have a considerable positive impact. A capital structure's capacity to moderate the effects of business risk, profitability, company size, and company growth on bond ratings is another benefit.